Induction of labour versus expectant monitoring for gestational hypertension or mild pre-eclampsia between 34 and 37 weeks' gestation (HYPITAT-II): a multicentre, open-label randomised controlled trial - Sporken Jan M J; Perquin Denise A M; Franssen Maureen T M; Wijnen-Duvekot Ella J; Willekes Christine; Oosterbaan Herman P; van Huizen Marloes E; van Beek Erik; Groot Christianne; Bloemenkamp Kitty W; Oudijk Martijn A; Porath Martina; et al. (BMC, 2011)
Abstract Background Gestational hypertension (GH) and pre-eclampsia (PE) can result in severe complications such as eclampsia, placental abruption, syndrome of Hemolysis, Elevated Liver enzymes and Low Platelets (HELLP) and ultimately even neonatal or maternal death. We recently showed that in women with GH or mild PE at term induction of labour reduces both high risk situations for mothers as well as the caesarean section rate. In view of this knowledge, one can raise the question whether women with severe hypertension, pre-eclampsia or deterioration chronic hypertension between 34 and 37 weeks of gestation should be delivered or monitored expectantly. Induction of labour might prevent maternal complications. However, induction of labour in late pre-term pregnancy might increase neonatal morbidity and mortality compared with delivery at term. Methods/Design Pregnant women with severe gestational hypertension, mild pre-eclampsia or deteriorating chronic hypertension at a gestational age between 34+0 and 36+6 weeks will be asked to participate in a multi-centre randomised controlled trial. Women will be randomised to either induction of labour or expectant monitoring. In the expectant monitoring arm, women will be induced only when the maternal or fetal condition detoriates or at 37+0 weeks of gestation. The primary outcome measure is a composite endpoint of maternal mortality, severe maternal complications (eclampsia, HELLP syndrome, pulmonary oedema and thromboembolic disease) and progression to severe pre-eclampsia. Secondary outcomes measures are respiratory distress syndrome (RDS), neonatal morbidity and mortality, caesarean section and vaginal instrumental delivery rates, maternal quality of life and costs. Analysis will be intention to treat. The power calculation is based on an expectant reduction of the maternal composite endpoint from 5% to 1% for an expected increase in neonatal RDS from 1% at 37 weeks to 10% at 34 weeks. This implies that 680 women have to be randomised. Discussion This trial will provide insight as to whether in women with hypertensive disorders late pre-term, induction of labour is an effective treatment to prevent severe maternal complications without compromising the neonatal morbidity. Trial Registration NTR1792 Clinical trial registration: http://www.trialregister.nl